Regulation of Polyphosphate Kinase Production by Antisense RNA in Pseudomonas fluorescens Pf0-1 - Silby, Mark W. (American Society for Microbiology, 2012)
Pseudomonas spp. adapt rapidly to environmental fluctuations. Loss or overproduction of polyphosphate reduces the fitness of Pseudomonas fluorescens Pf0-1, indicating the importance of the fine-tuning of polyphosphate production. An antisense RNA was investigated and shown to regulate the polyphosphate kinase gene (ppk) by a posttranscriptional mechanism reducing ppk transcript abundance.